Impact of Corporate Social Responsibility on Financial Performance of Listed Insurance Companies in Nigeria - Ahmad, Ado; Bwala, Nuhu James; Yusuf, Dunga Shizar (Kashere Journal of Management Sciences, 2024)
This study seeks to examine the impact of corporate social responsibility (CSR) on the financial performance of Listed Insurance Companies in Nigeria. To accomplish this, data were sourced from annual reports and accounts of the sampled insurance companies for the period of five (5) years (2013 to 2017). The data was analyzed using correlation coefficient and panel regression analysis. Findings indicated that there is a positive relationship between Corporate Social Responsibility (proxied by amount of money spent on education and environment) and financial performance. The research concludes that participation in Corporate Social Responsibility by companies is positively correlated with their financial performance indicators. It’s therefore recommended the companies to engaged in spending more on education and environment as their corporate social responsibility and to make sure that, the amount spent is properly disclosed in their annual reports and accounts.